2015
DOI: 10.4236/health.2015.71010
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Barriers to Contraceptive Use among Adolescents Aged 15 - 19 Years in Kenya: A Case Study of Nairobi

Abstract: Even after the launch of family planning program in Kenya, in 1967, contraceptive use among adolescents has remained below 10 percent while child bearing has increased from 2 percent at age 15 to 36 percent at age 19. To understand the roles of perceptions and barriers on contraceptive use, a mixed method study design was applied to a conceptual framework that operationalized these concepts using data from different sources of social interactions in Nairobi, Kenya. Quantitative data were collected from 1119 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 11 publications
2
37
2
Order By: Relevance
“…From the findings, the GEM scale seemed to work for CHC programme needs of depicting perceptions and attitudes among adolescents towards gender equitable norms. Our findings also support previous studies that demonstrate a link between HIV risks, teenage pregnancy risks and gender equitable norms (Kinaro ; Murigi et al . 2010; Pulerwitz and Barker ; Shattuck et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From the findings, the GEM scale seemed to work for CHC programme needs of depicting perceptions and attitudes among adolescents towards gender equitable norms. Our findings also support previous studies that demonstrate a link between HIV risks, teenage pregnancy risks and gender equitable norms (Kinaro ; Murigi et al . 2010; Pulerwitz and Barker ; Shattuck et al .…”
Section: Discussionsupporting
confidence: 92%
“…The unmet need for contraception is high among adolescent girls. In Kenya, 65 per cent of parents or guardians reportedly objected to contraceptive use by unmarried adolescents, and 68 per cent of the adolescents disapproved of contraceptive use by unmarried adolescents (Kinaro 2011). Childbearing beliefs indoctrinated among community members -such as "a man should have the final word about decisions in his home" -limit girls from using contraception if perceived as being bound to the will of her husband (Paek et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hulton [9], socio-cultural factors influence how decisions are made and the confidence to use contraceptives and other RH services [10]. Both theoretical and empirical literatures show that the influence of family or com-munity on adolescent behavior represents the central ways in which parents influence healthy adolescent development [11] [12]. Undesired perceptions could be as a result of myths and misconceptions acquired through socialization and interactions in the community [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Both theoretical and empirical literatures show that the influence of family or com-munity on adolescent behavior represents the central ways in which parents influence healthy adolescent development [11] [12]. Undesired perceptions could be as a result of myths and misconceptions acquired through socialization and interactions in the community [12] [13]. Evidence has shown that cultural values and beliefs of health care providers play a critical role in deciding whether or not to provide contraception to adolescents [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation